Integrated landscapes approaches – How are they defined, conceptualised, configured and operationalised and for what objectives: Perspectives from the four practices of distributed leadership practices? - Edward Gerald Ndilanha; Jan-Erik Jaensson; Raphael Gwahula (European Scientific Journal, ESJ, 2025)
While it is widely recognised that integrated landscape approaches are strategic management and leadership strategies used by project team leadership to design, develop and implement projects within integrated transboundary landscapes and seascapes, it is however, less clear how they are defined, conceptualised, configured and operationalised so as to achieve the desired outcomes. This study contributes to knowledge a new configuration and conceptualisation of the integrated transboundary landscapes and seascapes conceptual framework; the four principles of integrated landscape approaches (1) landscape partnership (2) shared understanding (3) vision and planning and (4) taking actions need to be seen as strategic management and leadership objectives of the activity systems. To achieve this, we explore the relationship between four principles of integrated landscape approaches (1) Landscape Partnership (2) Shared Understanding (3)Vision and Planning and (4) Taking Action as strategic management and leadership objectives drawing theoretical foundations from the four widely used distributed leadership practices: engaging leadership practice, developing leadership practice, enabling leadership practice and the empowering leadership practice. Implications for practitioners from the results of Exploratory Factor Analysis (EFA) and Confirmatory Factor Analysis (CFA) suggest the existence of a strong relationship between the integrated landscape approaches and the four practices of distributed leadership. It is revealed that (i) they draw from theoretical foundations; (ii) they are independent from one another; (iii) there is a very high level of cross-loading amongst them; (iv) they can be integrated into a form of a network of activity systems; (v) to function effectively and achieve desired outcomes they need to be enacted following an order of primacy; (vi) they are in the form of a normative decisio- making framework.